Microstructural changes of Fe-Cr-C/M(Nb,Ti)C composite coating produced by TIG method - Soner BUYTOZ (Gazi Üniversitesi Fen Bilimleri Dergisi, 2020)
Fe-Cr-C, Fe-Cr-C / FeNb and Fe-Cr-C / TiC coatings to investigate the effect of M7C3 and M (Nb, Ti) C carbides, Fe-based composite coating was prepared on the surface of medium carbon steel by gas tungsten arc technique. The microstructure and properties of the obtained composite coatings were examined using optical microscope and scanning electron microscope. While hexagonal-shapped and pointed-tipped M7C3 carbides were formed in the microstructure of FeCr-C coatings. in FeNb and TiC added coating layers, -(Fe, Cr) eutectic matrix solidified occured with both primary M7C3 carbides and triangular NbC, and quadrangular TiC grains.